(3GdefgL GdeSdhc aj SjGSI Gdedhcs - (3YHO GdQMef Hf fUQ Hf YHO Gddg, CHh GdfLjH, LdGd GdOjf GdYOhj GdTjRQj, fMh (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YLRJ GdYbhd Yf eYaQI PGJg LeYJ dNRGfI Ydheg gPG GdcJGH hgh jMJhi Ydi WQGja ef GdMceI hCUhd ai GdSjGSI s
(3BNQgG (B:s
(3hCeG GdWHbI GdKGdKI ef Gdedhc age GdCcKQhf bdhHge bSjI hCfaSge YUjI jDKQhf ddPGJ Ydi CehQ GdOjGfGJ hbO GfJgjfG s
(3Cdag dCHh GdeXaQ jhSa Hf CjhH Hf TGOi eMi OhdI CejQ GdeDefjf GdeJhai SfI (B589s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B197s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs